Magnesium-based composite material and method of forming the same

JP2025036373APending Publication Date: 2025-03-14ATW TECH INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024149006
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2024-08-30
Publication Date
2025-03-14

Smart Images

  • Figure 2025036373000001_ABST
    Figure 2025036373000001_ABST
Patent Text Reader

Abstract

To provide a magnesium-based composite material and a method of forming the same.SOLUTION: The method includes performing a melting process on magnesium, at least one first catalytic metal, and at least one first carbon allotrope to form a first magnesium-based solid solution; performing a severe plastic deformation on the first magnesium-based solid solution to form a second magnesium-based solid solution; and performing a high energy ball milling process on the second magnesium-based solid solution and an amorphous additive to form the magnesium-based composite material. The magnesium-based composite material includes a magnesium-based solid solution and the amorphous additive mixed with the magnesium-based solid solution. The magnesium-based solid solution includes magnesium, at least one first catalytic metal and at least one first carbon allotrope. The amorphous additive includes at least one second catalytic metal and at least one second carbon allotrope.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to magnesium-based composite materials and methods of forming same. [Background technology]

[0002] Hydrogen energy is a carbon-free energy, which can avoid the harm to the climate caused by carbon emissions. More and more related applications that rely on fossil fuels are being replaced by hydrogen energy, for example, the number of automobiles powered by hydrogen energy is continuously increasing. Therefore, suitable hydrogen carriers for storing and releasing hydrogen gas have become a major topic in the field. However, hydrogen carriers with better hydrogenation and dehydrogenation performance (e.g., high reversible capacity, speed, etc.) and methods for forming hydrogen carriers are still lacking. Therefore, more preferred hydrogen carrier materials and methods for forming them are needed. Summary of the Invention

[0003] The present disclosure provides a magnesium-based composite material comprising: a magnesium-based solid solution; and an amorphous additive mixed with the magnesium-based solid solution, the magnesium-based solid solution including magnesium, at least one first catalytic metal selected from the group consisting of aluminum, zinc, zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium, and at least one first carbon allotrope, and the amorphous additive including at least one second catalytic metal selected from the group consisting of zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium, and at least one second carbon allotrope.

[0004] In some embodiments, the weight percentage of the amorphous additive in the magnesium-based composite is between 1 wt% and 15 wt%.

[0005] In some embodiments, the weight percentage of each of the at least one first catalytic metal in the magnesium-based solid solution is less than or equal to 9 wt %.

[0006] In some embodiments, when the at least one first catalytic metal comprises aluminum, the weight percentage of the at least one first catalytic metal that is aluminum is at a maximum.

[0007] In some embodiments, the at least one first carbon allotrope and the at least one second carbon allotrope are independently selected from the group consisting of graphite, graphene, fullerenes, single-walled carbon nanotubes, multi-walled carbon nanotubes, activated carbon, and carbon black.

[0008] In some embodiments, the weight percentage of the at least one first carbon allotrope in the magnesium-based solid solution is less than or equal to 3 wt %.

[0009] In some embodiments, in the amorphous additive, the weight percentage of the at least one second carbon allotrope is greater than the weight percentage of the at least one second catalytic metal.

[0010] In some embodiments, the magnesium-based composite material has an average particle size between 20 μm and 80 μm.

[0011] In some embodiments, the average grain size within the magnesium-based solid solution is between 4 μm and 34 μm.

[0012] In some embodiments, the maximum reversible hydrogen storage capacity of the magnesium-based composite material is between 6 wt% and 7 wt%.

[0013] In some embodiments, the magnesium-based composite material has a hydrogen absorption rate between 2 wt% per minute and 4 wt% per minute, and the magnesium-based composite material has a hydrogen desorption rate between 0.25 wt% per minute and 1.25 wt% per minute.

[0014] The present disclosure further provides a method of forming a magnesium-based composite material, comprising: performing a melting process on magnesium, at least one first catalytic metal selected from the group consisting of aluminum, zinc, zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium, and at least one first carbon allotrope to form a first magnesium-based solid solution; performing a severe plastic deformation process on the first magnesium-based solid solution to form a second magnesium-based solid solution; and performing a high-energy ball milling process on the second magnesium-based solid solution and an amorphous additive including at least one second catalytic metal selected from the group consisting of zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium, and at least one second carbon allotrope to form the magnesium-based composite material.

[0015] In some embodiments, the dissolution process includes heating the magnesium, at least one first catalytic metal, and at least one first carbon allotrope at a temperature between 700°C and 800°C.

[0016] In some embodiments, the method further includes performing a homogenization process after the melting process and before the severe plastic deformation process, the homogenization process including heating the first magnesium-based solid solution at a temperature between 350°C and 450°C.

[0017] In some embodiments, the first average grain size in the first magnesium-based solid solution is larger than the second average grain size in the second magnesium-based solid solution, and the second average grain size is between 4 μm and 34 μm.

[0018] In some embodiments, the severe plastic deformation process includes pressurizing the first magnesium-based solid solution through an angled channel having a bend angle between 90° and 120°.

[0019] In some embodiments, the severe plastic deformation process includes repeatedly pressurizing the first magnesium-based solid solution through the angled channel, and the first magnesium-based solid solution not substantially rotating, rotating 90°, or rotating 180° along a longitudinal axis of the first magnesium-based solid solution between two successive passes through the angled channel.

[0020] In some embodiments, the severe plastic deformation process includes repeatedly pressing the first magnesium-based solid solution through the angled channel four to eight times.

[0021] In some embodiments, the high-energy ball milling process is carried out by a high-energy ball milling apparatus, and the rotation speed of the high-energy ball milling apparatus is 200 rpm to 500 rpm.

[0022] In some embodiments, the magnesium-based composite material has an average particle size between 20 μm and 80 μm. [Brief description of the drawings]

[0023] The present disclosure can be more fully understood from the following detailed description of the following embodiments and the drawings in which: [Figure 1] 1 is a flow chart of a method of forming a magnesium-based composite material according to some embodiments of the present disclosure. [Figure 2A] FIG. 1 is a schematic diagram of a severe plastic deformation process according to some embodiments of the present disclosure. [Figure 2B] FIG. 1 is a schematic diagram of a severe plastic deformation process according to some embodiments of the present disclosure. [Figure 2C] FIG. 1 is a schematic diagram of a severe plastic deformation process according to some embodiments of the present disclosure. [Figure 2D] FIG. 1 is a schematic diagram of a severe plastic deformation process according to some embodiments of the present disclosure. [Figure 3A]1A-1D are optical microscopy views of magnesium-based solid solutions following a dissolution process according to some embodiments of the present disclosure. [Figure 3B] FIG. 1 is an optical microscopy view of a magnesium-based solid solution after a homogenization process according to some embodiments of the present disclosure. [Figure 3C] 1A-1D are optical microscopy views of magnesium-based solid solutions after severe plastic deformation processes according to some embodiments of the present disclosure. [Figure 4A] 1A-1D are scanning electron microscopy images of magnesium-based composite materials during high energy ball milling process according to some embodiments of the present disclosure. [Figure 4B] FIG. 14 is a scanning electron micrograph of a magnesium-based composite material after a high energy ball milling process according to some embodiments of the present disclosure. [Diagram 5] 1 is a comparison of X-ray diffraction patterns according to some embodiments of the present disclosure and some comparative embodiments. [Figure 6A] FIG. 2 is a schematic diagram of hydrogen absorption capacity over time according to some embodiments of the present disclosure and some comparative embodiments. [Figure 6B] FIG. 2 is a schematic diagram of hydrogen desorption capacity over time according to some embodiments of the present disclosure and some comparative embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] In order to make the description of the present disclosure more detailed and complete, the following provides a brief description of various aspects of the embodiments and specific examples of the present disclosure.The present disclosure does not limit the embodiments to one form.The embodiments of the present disclosure may be combined or substituted with each other when beneficial, and may be added with other embodiments when not further described.

[0025] Spatially relative terms, such as top and bottom, may be used in this disclosure to describe the relationship of one element or feature to another element or feature in the drawings. Spatially relative terms are intended to include different orientations of the device in use or operation in addition to the orientation described in the drawings. For example, the device may be placed in other orientations (e.g., 90 degrees or other orientations). Thus, the spatially relative terms of this disclosure may be interpreted accordingly. Also, in this disclosure, unless otherwise stated, the same or similar reference numbers in different drawings refer to the same or similar elements formed in the same or similar manner from the same or similar materials.

[0026] The terms "approximately," "about," "about," "substantially," "essentially," and the like used in this disclosure include values, characteristics, and deviation ranges of said values, characteristics that may be understood by those skilled in the art. For example, taking into account the error of a value, characteristic, said terms may include values ​​within one or more standard deviation ranges (e.g., ±5%, ±10%, ±15%, ±20%, or ±30% of said value), or deviations between said characteristics and actual operation (e.g., "substantially parallel" means close to parallel in actual operation, not perfect parallel in an ideal case). Furthermore, an acceptable deviation range may be selected based on measurements or other characteristics, and there may not be only one deviation that applies to all values, characteristics.

[0027] The present disclosure provides a magnesium-based composite material. The magnesium-based composite material includes a magnesium-based solid solution and an amorphous additive mixed with the magnesium-based solid solution. The magnesium-based solid solution includes magnesium, at least one first catalytic metal selected from the group consisting of aluminum, zinc, zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium, and at least one first carbon allotrope. The amorphous additive includes at least one second catalytic metal selected from the group consisting of zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium, and at least one second carbon allotrope. The magnesium-based composite material of the present disclosure can be used as a hydrogen carrier, and has better hydrogenation and dehydrogenation performance, including higher reversible hydrogen storage capacity (e.g., 6wt%-7wt%), higher hydrogen absorption rate (e.g., 2wt%-4wt% per minute), higher hydrogen desorption rate (e.g., 0.25wt%-1.25wt% per minute), lower operating temperature (e.g., 300°C-400°C), etc. Next, the magnesium-based composite material of the present disclosure will be described in detail in the following embodiments.

[0028] The magnesium-based composite material of the present disclosure is a composite material including a magnesium-based solid solution and an amorphous additive. The magnesium-based solid solution and the amorphous additive have distinct characteristics. For example, the magnesium-based solid solution is a solid solution that exists in a solid state, includes magnesium, at least one first catalytic metal, and at least one first carbon allotrope that are uniformly mixed, and has a crystalline structure. Also, the amorphous additive is amorphous, non-crystalline, and disordered in atomic scale structure. The magnesium-based solid solution and the magnesium-based composite material mixed with the amorphous additive improve the hydrogenation and dehydrogenation performance of the magnesium-based composite material. For example, the hydrogen diffusion path in the magnesium-based composite material can be shortened, and the magnesium-based composite material includes a certain degree of structural defects to reduce the activation energy of hydrogen dissociation, etc. In some embodiments, the magnesium-based solid solution has a single crystal structure. In some embodiments, the crystal structure of the magnesium-based solid solution is hexagonal close-packed (HCP). In some embodiments, the average grain size of the crystal structure of the magnesium-based solid solution is 4 μm to 34 μm, for example, 4 μm, 9 μm, 14 μm, 19 μm, 24 μm, 29 μm, or 34 μm. The grain size-limited crystal structure has substantially the same crystal orientation (see, for example, Figures 3A, 3B, and 3C), so the boundaries between the grains mean that the crystal orientation changes. Small grain size means that there are more boundaries between the grains. In the microstructure, the average grain size within the above range provides suitable defects to have high hydrogen storage capacity and to reduce the activation energy of hydrogen dissociation. In some embodiments, the weight percentage of the preferred magnesium-based solid solution and the weight percentage of the preferred amorphous additive in the magnesium-based composite are 85 wt% to 99 wt% (e.g., 85 wt%, 87 wt%, 89 wt%, 91 wt%, 93 wt%, 95 wt%, 97 wt% or 99 wt%) and 1 wt% to 15 wt% (e.g., 1 wt%, 3 wt%, 5 wt%, 7 wt%, 9 wt%, 11 wt%, 13 wt% or 15 wt%), respectively.

[0029] The magnesium-based composite material of the present disclosure will be further described in detail based on some embodiments. In some embodiments, the magnesium-based composite material is present in the form of particles to increase the surface area of ​​the magnesium-based composite material. A large surface area improves hydrogenation and dehydrogenation performance, for example, when the formation and decomposition of magnesium hydride occurs, there can be more magnesium nucleation sites and shorter hydrogen diffusion paths, thereby increasing the absorption and desorption rate of hydrogen gas. In addition, in the case of a magnesium-based composite material with a large surface area, small deformation can occur during the formation and decomposition of magnesium hydride to reduce the explosion that may occur when the magnesium-based composite material is heated. In some embodiments, the average particle size of the magnesium-based composite material with improved hydrogenation and dehydrogenation performance is preferably 20 μm to 80 μm, for example 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 50 μm, 60 μm, 70 μm or 80 μm.

[0030] The magnesium-based composite material of the present disclosure will be further described in detail based on some embodiments. In some embodiments, the maximum reversible (i.e., hydrogen can be reversibly absorbed and desorbed) hydrogen storage capacity of the magnesium-based composite material is 6 wt% to 7 wt%, for example, 6.0 wt%, 6.2 wt%, 6.4 wt%, 6.6 wt%, 6.8 wt%, or 7.0 wt%. In some embodiments, the hydrogen absorption rate of the magnesium-based composite material is 2 wt% per minute to 4 wt% per minute, for example, 2.0 wt% per minute, 2.5 wt% per minute, 3.0 wt% per minute, 3.5 wt% per minute, or 4.0 wt% per minute. In some embodiments, the hydrogen desorption rate of the magnesium-based composite material is between 0.25 wt% per minute and 1.25 wt% per minute, such as 0.25 wt% per minute, 0.50 wt% per minute, 0.75 wt% per minute, 1.00 wt% per minute, or 1.25 wt% per minute. In some embodiments, the maximum reversible hydrogen storage capacity, hydrogen absorption rate, and hydrogen desorption rate are measured at an operating temperature of 300° C. to 400° C., such as 300° C., 320° C., 340° C., 360° C., 380° C., or 400° C., and a hydrogen gas pressure of 2.5 MPa to 3.5 MPa, such as 2.5 MPa, 2.7 MPa, 2.9 MPa, 3.1 MPa, 3.3 MPa, or 3.5 MPa.

[0031] Next, the magnesium-based solid solution will be described in detail according to some embodiments. The magnesium-based solid solution includes magnesium having high hydrogen storage capacity, at least one first catalytic metal as a catalyst for improving hydrogen dissociation from magnesium, and at least one first carbon allotrope providing a larger surface area to enhance the kinetic rate of hydrogen absorption and desorption. In some embodiments, the weight percentage of magnesium in the magnesium-based solid solution is preferably 85 wt% or more in order to have high hydrogen storage capacity and to enhance the uniformity of the solid solution. In some embodiments, the at least one first catalytic metal is preferably selected from the group consisting of aluminum, zinc, zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium. In some embodiments, the weight percentage of each of the at least one first catalytic metal in the magnesium-based solid solution is preferably 9 wt% or less in order to improve the catalytic effect and enhance the uniformity of the solid solution. In some embodiments, the at least one first carbon allotrope is preferably selected from the group consisting of graphite, graphene, fullerene, single-walled carbon nanotubes, multi-walled carbon nanotubes, activated carbon, and carbon black. In some embodiments, the weight percentage of the at least one first carbon allotrope in the magnesium-based solid solution is preferably 3 wt% or less to increase the kinetic rate and to increase the homogeneity of the solid solution.

[0032] Some embodiments further describe the magnesium-based solid solution of the present disclosure in detail. In some embodiments, the weight percentage of aluminum is the highest among the at least one first catalytic metal to have a better catalytic effect. In some embodiments, the weight percentage of aluminum in the magnesium-based solid solution is preferably 3 wt% to 9 wt%, for example, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, or 9 wt%. In some embodiments, the weight percentage of zinc in the magnesium-based solid solution is preferably 0.5 wt% to 6 wt%, for example, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, or 6 wt%. In some embodiments, the weight percentage of zirconium in the magnesium-based solid solution is preferably 0.1 wt% to 1.6 wt%, for example, 0.1 wt%, 0.6 wt%, 1.0 wt%, 1.3 wt%, or 1.6 wt%. In some embodiments, the weight percentage of nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, or yttrium in the magnesium-based solid solution is preferably 0.1 wt% to 1 wt%, such as 0.1 wt%, 0.25 wt%, 0.5 wt%, 0.75 wt%, or 1 wt%. More specifically, in some embodiments, the at least one first catalytic metal comprises aluminum, zinc, and at least one selected from the group consisting of zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium, and the weight ratio of aluminum to zinc is preferably 3:1 to 9:1, such as 3:1, 6:1, or 9:1. More specifically, in some embodiments, the at least one first catalytic metal comprises zinc, zirconium, and at least one selected from the group consisting of nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium, and the weight ratio of zinc to zirconium is preferably from 3:1 to 60:1, such as 3:1, 5:1, 10:1, 20:1, 30:1, 40:1, 50:1, or 60:1.When the at least one first catalytic metal comprises aluminum and zinc, or zinc and zirconium, it is advantageous to further improve the mechanical properties (e.g., higher tensile strength, higher yield strength, etc.), enhance the corrosion resistance, and enhance the application properties (e.g., better welding performance, etc.) of the magnesium-based solid solution. In some embodiments, the weight percentage of the at least one first carbon allotrope in the magnesium-based solid solution is preferably 1 wt% to 3 wt%, for example 1.0 wt%, 1.5 wt%, 2.0 wt%, 2.5 wt% or 3.0 wt%. In some embodiments, the at least one first carbon allotrope comprises multi-walled carbon nanotubes, and the density of each multi-walled carbon nanotube is preferably 0.01 g / cm. 3 ~0.1g / cm 3 , e.g. 0.01g / cm 3 , 0.04g / cm 3 , 0.06g / cm 3 , 0.08g / cm 3 or 0.10 g / cm 3 It is.

[0033] Next, the amorphous additive will be described in detail according to some embodiments. The amorphous additive includes at least one second catalytic metal as a catalyst for improving the dissociation of hydrogen from magnesium, and at least one second carbon allotrope that provides a larger surface area to enhance the kinetic rate of hydrogen absorption and desorption. In some embodiments, the at least one second catalytic metal is preferably selected from the group consisting of zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium. In some embodiments, the weight percentage of the at least one second catalytic metal in the amorphous additive is preferably 35 wt% to 45 wt%, for example 35 wt%, 37 wt%, 40 wt%, 43 wt%, or 45 wt%, to improve the catalytic effect. In some embodiments, the at least one second carbon allotrope is preferably selected from the group consisting of graphite, graphene, fullerene, single-walled carbon nanotubes, multi-walled carbon nanotubes, activated carbon, and carbon black. In some embodiments, the weight percentage of the at least one second carbon allotrope in the amorphous additive is preferably 55 wt% to 65 wt%, for example 55 wt%, 57 wt%, 60 wt%, 63 wt% or 65 wt%, to enhance the kinetic rate. In some embodiments, the at least one first carbon allotrope and the at least one second carbon allotrope are the same. In some embodiments, the at least one first carbon allotrope and the at least one second carbon allotrope are different. In some embodiments, the weight percentage of the at least one second carbon allotrope is greater than the weight percentage of the at least one second catalytic metal to facilitate the formation of the particulate magnesium-based composite and the desired structural defects in the magnesium-based composite (see the method of forming a magnesium-based composite below for details). In some embodiments, the weight ratio of the at least one second carbon allotrope to the at least one second catalytic metal is preferably from 1.1:1 to 2.5:1, such as 1.1:1, 1.3:1, 1.5:1, 1.7:1, 1.9:1, 2.1:1, 2.3:1, or 2.5:1.

[0034] The present disclosure further provides a method for forming the above magnesium-based composite material, which comprises: performing a melting process on magnesium, at least one first catalytic metal selected from the group consisting of aluminum, zinc, zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium, and at least one first carbon allotrope to form a first magnesium-based solid solution; performing a severe plastic deformation process on the first magnesium-based solid solution to form a second magnesium-based solid solution; and performing a high-energy ball milling process on the second magnesium-based solid solution, and an amorphous additive including at least one second catalytic metal selected from the group consisting of zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium, and at least one second carbon allotrope to form a magnesium-based composite material. The magnesium-based composite material formed by the method of the present disclosure can be used as a hydrogen carrier and has better hydrogenation and dehydrogenation performance as described above. The details of the magnesium-based composite material may not be described later. In addition to being able to form the magnesium-based composite material of the present disclosure, the method of the present disclosure is easy to implement and can mass-produce the magnesium-based composite material. Next, the method of the present disclosure will be described in detail in the following embodiments.

[0035] In the flow chart shown in Figure 1, the method 100 of the present disclosure includes operation 101 of performing a dissolution process on magnesium, at least one first catalytic metal, and at least one first carbon allotrope to form a first magnesium-based solid solution. The first magnesium-based solid solution is substantially the same as the magnesium-based solid solution described above, except that, for example, the mechanical properties of the first magnesium-based solid solution may be different and the first magnesium-based solid solution may have a larger first average grain size of the crystal structure (see operation 102 below for details). In some embodiments, the first average grain size is between 90 μm and 150 μm, for example, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, or 150 μm. In some embodiments, the preferred dissolution process includes heating the magnesium, the at least one first catalytic metal, and the at least one first carbon allotrope at a temperature between 700° C. and 800° C., for example, 700° C., 720° C., 740° C., 760° C., 780° C., or 800° C., to enhance the uniformity of the solid solution formed. In some embodiments, the dissolution process is carried out by an induction furnace to enhance the efficiency of the solid solution formation and promote the mass production of the solid solution. In some embodiments, the dissolution process further includes stirring the magnesium, the at least one first catalytic metal, and the at least one first carbon allotrope, and the stirring time is preferably between 10 minutes and 20 minutes, for example, 10 minutes, 15 minutes, or 20 minutes, to enhance the uniformity of the solid solution formed. In some embodiments, the dissolution process includes heating the magnesium, the at least one first catalytic metal, and the at least one first carbon allotrope at a temperature between 700° C. and 800° C., for example, 700° C., 720° C., 740° C., 760° C., 780° C., or 800° C. ... 6 ) and carbon dioxide (CO 2 In some embodiments, the melting process further includes performing a quench at room temperature, e.g., 20°C to 30°C, e.g., 20°C, 22°C, 24°C, 26°C, 28°C, or 30°C, to harden the first magnesium-based solid solution. In some embodiments, the melting process further includes performing a quench at room temperature, e.g., 20°C to 30°C, e.g., 20°C, 22°C, 24°C, 26°C, 28°C, or 30°C, to harden the first magnesium-based solid solution.

[0036] In some embodiments, the method 100 further includes performing a homogenization process after operation 101 and before operation 102. The homogenization process makes the brittle first magnesium-based solid solution formed by operation 101 more ductile. Thus, the more ductile first magnesium-based solid solution can be more easily implemented in operation 102 to reduce the grain size of the first magnesium-based solid solution (see operation 102 below for details). It should be noted that the homogenization process increases the homogeneity of the solid solution by reducing the fractures in the crystal structure of the first magnesium-based solid solution, so that the second magnesium-based solid solution formed in operation 102 not only has a reduced grain size, but also has limited fractures to enhance the diffusion of hydrogen gas in the solid solution. The changes in the crystal structure after operation 101, after the homogenization process, and after operation 102 are described in detail in the examples shown in Figures 3A, 3B, and 3C. In some embodiments, the preferred homogenization process includes heating the first magnesium-based solid solution at a temperature between 350° C. and 450° C. (e.g., 350° C., 370° C., 390° C., 410° C., 430° C., or 450° C.), and the time length is preferably between 20 hours and 30 hours (e.g., 20 hours, 22 hours, 24 hours, 26 hours, 28 hours, or 30 hours). In some embodiments, the heating temperature of the homogenization process is lower than the heating temperature of the dissolution process of operation 101. In some embodiments, the heating time of the homogenization process is longer than the heating time of the dissolution process of operation 101.

[0037] In some embodiments, method 100 further includes performing an aqua-knife process after operation 101 and before operation 102. The aqua-knife process includes cutting the first magnesium-based solid solution into strips in preparation for operation 102. For example, in operation 102, each strip of the first magnesium-based solid solution is pressed into an angled channel to adjust the mechanical properties and grain size of the solid solution (see operation 102 below for details). In some embodiments, the length of each strip of the first magnesium-based solid solution is between 5 mm and 15 mm, e.g., 11.5 mm, the width of each strip of the first magnesium-based solid solution is between 5 mm and 15 mm, e.g., 11.5 mm, and the height of each strip of the first magnesium-based solid solution is between 70 mm and 80 mm, e.g., 75 mm.

[0038] In the flow chart shown in FIG. 1, the method 100 of the present disclosure includes an operation 102 of performing a severe plastic deformation process on a first magnesium-based solid solution to form a second magnesium-based solid solution. The second magnesium-based solid solution is substantially identical to the magnesium-based solid solution. For example, a second average grain size of the crystal structure of the second magnesium-based solid solution is substantially identical to the average grain size of the crystal structure of the magnesium-based solid solution and is smaller than the first average grain size of the crystal structure of the first magnesium-based solid solution. The severe plastic deformation strains the first magnesium-based solid solution, thereby changing the mechanical properties of the first magnesium-based solid solution. On a microstructural scale, the grain size of the first magnesium-based solid solution is reduced. FIGS. 2A, 2B, 2C, and 2D are examples of performing a severe plastic deformation process according to some embodiments. In FIGS. 2A, 2B, 2C, and 2D, the severe plastic deformation process includes compressing the first magnesium-based solid solution 201 through an angled channel 202. In some examples, the angled channel 202 is folded and has a folding angle φ that is preferably between 90° and 120°, e.g., 90°, 100°, 110°, or 120°. In some embodiments, the severe plastic deformation process includes repeatedly pressing the first magnesium-based solid solution 201 through the angled channel 202, and between two successive passes, the first magnesium-based solid solution 201 does not substantially rotate along the long axis 203 (e.g., FIG. 2A), rotates 90° along the long axis 203 (e.g., FIG. 2B and FIG. 2C), or rotates 180° along the long axis 203 (e.g., FIG. 2D). The distinction between FIG. 2B and FIG. 2C is that each time the first magnesium-based solid solution 201 rotates, the direction of rotation in FIG. 2B changes, but the direction of rotation in FIG. 2C does not substantially change. Specifically, in Figure 2B, after the first pass the direction of rotation along major axis 203 is clockwise, but after the second pass the direction of rotation along major axis 203 is counterclockwise. Specifically, in Figure 2C, after every pass the direction of rotation along major axis 203 remains either clockwise or counterclockwise.In some embodiments, the number of repetitions of pressurizing the first magnesium-based solid solution 201 to pass through the angled channel 202 is preferably 4 to 8 times, such as 4, 5, 6, 7 or 8 times. In some embodiments, the temperature at which the first magnesium-based solid solution 201 is pressurized to pass through the angled channel 202 is preferably 300°C to 350°C, such as 300°C, 310°C, 320°C, 330°C, 340°C or 350°C. In some embodiments, a pressure of preferably 150kg to 250kg, such as 150kg, 170kg, 190kg, 210kg, 230kg or 250kg is applied to the first magnesium-based solid solution 201 to pass through the angled channel 202. In some embodiments, the speed at which the first magnesium-based solid solution 201 is forced through the angled channel 202 is preferably between 0.5 mm per second and 2.0 mm per second, such as 0.5 mm per second, 1.0 mm per second, 1.5 mm per second, or 2.0 mm per second.

[0039] In some embodiments, method 100 may further include performing a grinding process after operation 102 and before operation 103. The grinding process includes manually grinding the second magnesium-based solid solution into particles in preparation for operation 103. In some embodiments, the particle size of the second magnesium-based solid solution after the grinding process is preferably between 80 μm and 120 μm, for example 80 μm, 90 μm, 100 μm, 110 μm, or 120 μm.

[0040] In the flow chart shown in FIG. 1, the method 100 of the present disclosure includes an operation 103 of performing a high energy ball milling process on the second magnesium-based solid solution and the amorphous additive to form a magnesium-based composite material. The amorphous additive, in addition to contributing to obtain better hydrogenation and dehydrogenation performance as described above, further contributes to obtain the microstructure of the magnesium-based composite material in operation 103, such as the desired average particle size as described above. In some embodiments, the high energy ball milling process is performed by a high energy ball milling apparatus (e.g., a planetary ball milling apparatus) to grind and mix the second magnesium-based solid solution and the amorphous additive. In some embodiments, the high energy ball milling apparatus includes grinding balls located in a grinding tank to impact the second magnesium-based solid solution and the amorphous additive to reduce the particle size. In some embodiments, the grinding balls are preferably steel balls. In some embodiments, the weight ratio of the weight of the grinding balls to the total weight of the second magnesium-based solid solution and the amorphous additive is preferably 30:1 to 50:1, such as 30:1, 40:1, or 50:1. In some embodiments, the rotation speed of the high energy ball milling apparatus is preferably 200 rpm to 500 rpm, for example 200 rpm, 300 rpm, 400 rpm or 500 rpm, in order to increase the impact energy applied to the second magnesium-based solid solution and the amorphous additive by applying centrifugal force to the grinding balls, the second magnesium-based solid solution and the amorphous additive. In some embodiments, the total rotation time of the high energy ball milling apparatus is preferably 4 hours to 16 hours, for example 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours or 16 hours. In some embodiments, the rotation direction is changed every 30 minutes, stopped for 10 minutes before the next rotation, for example rotating clockwise for 30 minutes, remaining stationary for 10 minutes, and then rotating counterclockwise for 30 minutes.

[0041] The magnesium-based composite material and the method of forming the same are described in detail in the following examples, which are intended to provide a better understanding of the contents of the present disclosure without intending to limit the scope of the present disclosure.

[0042] In Example 1, the magnesium-based composite material was made of 92.5 wt% magnesium, 3 wt% aluminum, 1 wt% zinc, 0.5 wt% titanium, and 3 wt% multi-walled carbon nanotubes (each multi-walled carbon nanotube had a density of about 0.057 g / cm 3 The magnesium-based solid solution contained 96 wt% of a magnesium-based solid solution containing 40 wt% nickel and 60 wt% graphene, and 4 wt% of an amorphous additive containing 40 wt% nickel and 60 wt% graphene. Magnesium, aluminum, zinc, titanium and multi-walled carbon nanotubes were heated at 760°C and stirred for 15 minutes in a dissolution process in operation 101 to obtain a first magnesium-based solid solution. The first magnesium-based solid solution was heated at 410°C for 24 hours in a homogenization process. The first magnesium-based solid solution was cut into strips with a length of 11.5 mm, a width of 11.5 mm and a height of 75 mm in an aqua knife process. In a severe plastic deformation process in operation 102, the first magnesium-based solid solution was pressed through an angled channel with a bending angle of 120° by applying 210 kg at a speed of 1.0 mm per second. The second magnesium-based solid solution obtained by operation 102 was mixed with nickel and graphene in a high-energy ball mill process in operation 103. The weight ratio of the steel ball weight in the grinding tank of the high-energy ball mill apparatus to the total weight of the second magnesium-based solid solution, nickel and graphene was 40:1, the rotation speed of the high-energy ball mill apparatus was 400 rpm, the rotation direction was changed every 30 minutes, and stopped for 10 minutes before the next rotation.

[0043] 3A, 3B and 3C are optical microscope images of the magnesium-based solid solution of Example 1 after operation 101, after the homogenization process and after operation 102, respectively. FIG. 3A, 3B and 3C clearly show the layered eutectic crystal structure of the solid solution. The fracture of the crystal structure of FIG. 3B is obviously reduced compared to FIG. 3A. Therefore, the cracks generated after operation 102 are limited compared to the method without the homogenization process. In addition, the grain size of the crystal structure of FIG. 3C is smaller than that of FIG. 3A and FIG. 3B.

[0044] 4A and 4B were scanning electron micrographs of the magnesium-based composite material of Example 1 during and after the high-energy ball milling process, respectively. The particles exhibited a sawtooth shape during the high-energy ball milling process, and were highly dispersed and had the desired particle size after the high-energy ball milling process was completed.

[0045] Example 1 was compared with Comparative Example 1. Comparative Example 1 was almost the same as Example 1, except that Comparative Example 1 did not include Operation 102 and Operation 103, while Example 1 included Operation 101, Operation 102, and Operation 103. In other words, in Comparative Example 1, only a first magnesium-based solid solution was formed, while in Example 1, a magnesium-based composite material was formed.

[0046] 5 is a comparison of the X-ray diffraction patterns of Comparative Example 1 and Example 1, where curves C1 and C3 are the X-ray diffraction patterns of the first magnesium-based solid solution of Comparative Example 1 before and after hydrogenation, respectively, and curves C2 and C4 are the X-ray diffraction patterns of the magnesium-based composite material of Example 1 before and after hydrogenation, respectively. The symbols ◆, ┼, ▼, and ■ in FIG. 5 represent the corresponding Mg, Al, 12 Mg 17 , Ni and MgH 2 Before hydrogenation, the peaks of curve C2 were broader than those of curve C1, and the peaks of curve C2 contained the corresponding Ni peaks. After hydrogenation, curve C4 showed a stronger MgH peak than curve C3. 2 and the Mg in Example 1 is substantially MgH 2 was completely converted to

[0047] 6A and 6B are comparisons of the time course of hydrogen absorption and desorption capacities measured by a Sievert type constant volume equipment at an operating temperature of 350° C. and a hydrogen gas pressure of 3 MPa, where curves C5 and C7 correspond to Comparative Example 1, and curves C6 and C8 correspond to Example 1. The maximum reversible hydrogen storage capacity of Example 1 (e.g., about 6.48 wt%) was much higher than the maximum reversible hydrogen storage capacity of Comparative Example 1 (e.g., about 5.24 wt%). In addition, the hydrogen absorption rate of Example 1 (e.g., about 3.4614 wt% per minute) was much faster than the hydrogen absorption rate of Comparative Example 1 (e.g., about 0.0873 wt% per minute), and the hydrogen desorption rate of Example 1 (e.g., about 0.7660 wt% per minute) was also much faster than the hydrogen desorption rate of Comparative Example 1 (e.g., about 0.1638 wt% per minute).

[0048] The average grain size of the magnesium-based solid solution in Example 2A to Example 2H, Comparative Example 2I, Example 3A to Example 3H and Comparative Example 3I was compared in Table 1 below. Example 2A to Example 2H were almost the same as Example 1 above, except that the operation 102 in each example may be different. For example, the operations of Example 2A to Example 2B were performed as shown in FIG. 2A, the number of repetitions of Example 2A was 4, and the number of repetitions of Example 2B was 8, the operations of Example 2C to Example 2D were performed as shown in FIG. 2B, the number of repetitions of Example 2C was 4, and the number of repetitions of Example 2D was 8, the operations of Example 2E to Example 2F were performed as shown in FIG. 2C, the number of repetitions of Example 2E was 4, and the number of repetitions of Example 2F was 8, and the operations of Example 2G to Example 2H were performed as shown in FIG. 2D, the number of repetitions of Example 2G was 4, and the number of repetitions of Example 2H was 8. Comparative Example 2I was similar to Example 1 above, except that only one iteration through the angled channel was performed in performing operation 102. Examples 2A-2H had more favorable and smaller average grain sizes than Comparative Example 2I. Each of Examples 3A-3H was similar to Examples 2A-2H above, except that the weight percentages of magnesium and aluminum may differ. In Examples 3A-3H, the weight percentage of magnesium was 89.5 wt% and the weight percentage of aluminum was 6 wt%. Comparative Example 3I was similar to Comparative Example 2I, except that the weight percentage of magnesium in Comparative Example 3I was 89.5 wt% and the weight percentage of aluminum was 6 wt%. Examples 3A-3H had more favorable and smaller average grain sizes than Comparative Example 3I.

[0049] [Table 1]

[0050] The magnesium-based composite materials of the present disclosure and the magnesium-based composite materials formed by the methods of the present disclosure have better hydrogenation and dehydrogenation performance, including higher reversible hydrogen storage capacity, higher hydrogen absorption rate, higher hydrogen desorption rate, lower operating temperature, etc. The methods of the present disclosure are also easy to implement, can be carried out in large quantities, and materials are readily available.

[0051] Although the present disclosure has been described in detail with respect to certain embodiments, other embodiments may be realized, and therefore the scope and spirit of the appended claims should not be limited by the description of the embodiments of the present disclosure.

[0052] Those skilled in the art can modify and change the contents of the present disclosure without departing from the scope and spirit of the present disclosure. As long as these modifications and changes are included in the scope and spirit of the appended claims, the present disclosure also intends to cover these modifications and changes. [Explanation of symbols]

[0053] 100: Method 101~103: Operation 201: First magnesium solid solution 202: Angled Channel 203:Long axis C1~C8:Curve φ: Bending angle

Claims

1. Magnesium and at least one first catalytic metal selected from the group consisting of aluminum, zinc, zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium; at least one first carbon allotrope; A magnesium-based solid solution comprising: mixed with the magnesium-based solid solution, at least one second catalytic metal selected from the group consisting of zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium; at least one second carbon allotrope; and an amorphous additive comprising A magnesium-based composite material comprising:

2. The magnesium-based composite material according to claim 1 , wherein the weight percentage of the amorphous additive in the magnesium-based composite material is 1 wt % to 15 wt %.

3. 10. The magnesium-based composite material of claim 1, wherein the weight percentage of each of said at least one first catalytic metal in said magnesium-based solid solution is less than or equal to 9 wt%.

4. 10. The magnesium-based composite material of claim 1, wherein when said at least one first catalytic metal comprises aluminum, the weight percentage of said at least one first catalytic metal that is aluminum is at a maximum.

5. 2. The magnesium-based composite material of claim 1, wherein the at least one first carbon allotrope and the at least one second carbon allotrope are independently selected from the group consisting of graphite, graphene, fullerenes, single-walled carbon nanotubes, multi-walled carbon nanotubes, activated carbon, and carbon black.

6. 2. The magnesium-based composite material of claim 1, wherein a weight percentage of said at least one first carbon allotrope in said magnesium-based solid solution is less than or equal to 3 wt%.

7. 10. The magnesium-based composite material of claim 1, wherein in said amorphous additive, a weight percentage of said at least one second carbon allotrope is greater than a weight percentage of said at least one second catalytic metal.

8. The magnesium-based composite material according to claim 1, wherein the average particle size of the magnesium-based composite material is 20 μm to 80 μm.

9. 2. The magnesium-based composite material of claim 1, wherein the average grain size within the magnesium-based solid solution is between 4 μm and 34 μm.

10. 2. The magnesium-based composite material of claim 1, wherein the maximum reversible hydrogen storage capacity of the magnesium-based composite material is 6 wt% to 7 wt%.

11. 2. The magnesium based composite material of claim 1, wherein the magnesium based composite material has a hydrogen absorption rate of 2 wt % per minute to 4 wt % per minute, and a hydrogen desorption rate of 0.25 wt % per minute to 1.25 wt % per minute.

12. performing a dissolution process on magnesium, at least one first catalytic metal selected from the group consisting of aluminum, zinc, zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium, and at least one first carbon allotrope to form a first magnesium-based solid solution; performing a severe plastic deformation process on the first magnesium-based solid solution to form a second magnesium-based solid solution; performing a high energy ball milling process on the second magnesium-based solid solution and an amorphous additive comprising at least one second catalytic metal selected from the group consisting of zirconium, nickel, titanium, vanadium, chromium, cobalt, iron, copper, molybdenum, niobium, palladium, and yttrium, and at least one second allotrope of carbon, to form the magnesium-based composite material; 1. A method for forming a magnesium-based composite material comprising:

13. 13. The method of claim 12, wherein the dissolution process comprises heating the magnesium, the at least one first catalytic metal and the at least one first carbon allotrope at a temperature between 700°C and 800°C.

14. 13. The method of claim 12, further comprising performing a homogenization process after the melting process and before the severe plastic deformation process, wherein the homogenization process comprises heating the first magnesium-based solid solution at a temperature between 350°C and 450°C.

15. 13. The method of claim 12, wherein a first average grain size in the first magnesium-based solid solution is larger than a second average grain size in the second magnesium-based solid solution, and the second average grain size is between 4 μm and 34 μm.

16. 13. The method of claim 12, wherein the severe plastic deformation process comprises pressing the first magnesium-based solid solution through an angled channel having a bend angle of between 90° and 120°.

17. 13. The method of claim 12, wherein the severe plastic deformation process comprises repeatedly pressurizing the first magnesium-based solid solution through an angled channel and substantially no rotation, a 90° rotation, or a 180° rotation along a longitudinal axis of the first magnesium-based solid solution between two successive passes of the first magnesium-based solid solution through the angled channel.

18. 13. The method of claim 12, wherein the severe plastic deformation process comprises repeatedly pressing the first magnesium-based solid solution through an angled channel between 4 and 8 times.

19. 13. The method of claim 12, wherein the high-energy ball milling process is carried out by a high-energy ball milling device, and the rotation speed of the high-energy ball milling device is 200 rpm to 500 rpm.

20. The method of claim 12, wherein the magnesium-based composite material has an average grain size of 20 μm to 80 μm.

Citation Information

Patent Citations

  • Magnesium-yttrium-zinc hydrogen storage magnesium alloy and preparation method thereof

    CN111101041A

  • High-capacity magnesium-based composite hydrogen storage material and preparation method thereof

    CN111515380A

  • Hydrogen-absorbing composite material and its manufacturing method

    JP2003138333A

  • Hydrogen storage material, its production method, and hydrogen generator

    JP2005054243A

  • Catalytic hydrogen desorption in mg-based hydrogen storage materials and method of making the same

    JP2007522917A